2021
DOI: 10.1021/acsphotonics.1c00012
|View full text |Cite
|
Sign up to set email alerts
|

2.5D Microscopy: Fast, High-Throughput Imaging via Volumetric Projection for Quantitative Subcellular Analysis

Abstract: Imaging-based single-cell analysis is essential to study the expression level and functions of biomolecules at subcellular resolution. However, its low throughput has prevented the measurement of numerous cellular features from multiples cells in a rapid and efficient manner. Here we report 2.5D microscopy that significantly improves the throughput of fluorescence imaging systems while maintaining high-resolution and single-molecule sensitivity. Instead of sequential z-scanning, volumetric information is proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Because the lateral resolution is inversely proportional to the numerical aperture (NA), this technique employs high-NA objectives, which considerably limits its natural depth-of-field (DoF). Several groups have demonstrated that placing a phase mask in the aperture stop of a localization microscope can significantly increase its DoF [2][3][4][5]. Recently, we have proposed to use annular binary phase masks to extend 2Dlocalization performance within a prescribed DoF range [6,7] (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Because the lateral resolution is inversely proportional to the numerical aperture (NA), this technique employs high-NA objectives, which considerably limits its natural depth-of-field (DoF). Several groups have demonstrated that placing a phase mask in the aperture stop of a localization microscope can significantly increase its DoF [2][3][4][5]. Recently, we have proposed to use annular binary phase masks to extend 2Dlocalization performance within a prescribed DoF range [6,7] (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2, E2E-BPF outperforms all the reference pupil designs in terms of RMSE, SSIM, and DoF-extension ability. Notably, compared with the binary phase structure that has recently been applied to DoF-extension uorescence microscope 37 Experimental performance evaluation: uorescence microspheres…”
Section: T î Zmentioning
confidence: 99%
“…Lensless imaging systems enable large DOF extension 138 , broadband achromatic imaging 139 , 3D imaging 140 , and microscopy 141 . Planar optics can also be used as phase modulation devices in super resolution microscopy 142 or wavefront coding systems 81,[143][144][145] . Similarly, with the addition of deep optics, the speed and quality of lensless imaging can be enhanced 146,147 .…”
Section: Other Psf Engineering Techniquesmentioning
confidence: 99%